Time-Related Rulings in Fiqh Munakahat: A Contemporary Integration of Astronomical and Jurisprudential Analysis - Badrun Taman; Fatimah; Friska Linia Sari; Abdul Gafar Olawale Fahm (Faculty of Sharia, IAIN Metro, 2025)
This study examines time-related rulings in Fiqh Munakahat (Islamic family law), focusing on key provisions such as iddah (waiting period after divorce or death), baligh (age of maturity), hadlanah (child custody), and radla’ah (breastfeeding period). Although these rulings are normatively based on the lunar (qamariyah) calendar, their implementation in Indonesia often relies on Gregorian approximations, leading to inconsistencies in legal outcomes—particularly in matters of remarriage, inheritance, and personal status. Using a qualitative library-based approach, this study integrates classical fiqh sources with astronomical computation (Ilmu Falak) and judicial case analysis from Indonesian Religious Courts. The integration is conducted by converting Gregorian-based legal timeframes into hilal-based lunar calculations and comparing the outcomes with statutory norms such as the Compilation of Islamic Law (KHI). This method highlights practical and doctrinal mismatches not addressed in prior studies, especially regarding standardizing iddah durations. The findings demonstrate that Gregorian approximations often arbitrarily extend or shorten legal periods, undermining legal certainty and compliance with Islamic jurisprudence. By contrast, lunar-based reckoning offers higher precision and is more faithful to scriptural mandates. The study recommends revising national legal instruments and court practices to adopt hilal-based time calculations in marital rulings, thus enhancing consistency, legitimacy, and contextual relevance in contemporary Islamic legal systems.